Fabrication and Performances of Graphene/TiO2 Composites Derived from Graphenes and Titanium(IV) Alkoxide Precursors - Ye, Shu; Ullah, Kefayat; Zhu, Lei; Jo, Sun-Bok; Cho, Kwang-Youn; Oh, Won-Chun (Asian Journal of Chemistry, 2014)
Graphene/TiO2 composites were synthesized by sol-gel technique using titanium(IV) n-butoxide (TNB), titanium(IV) isopropoxide (TIP) and titanium(IV) propoxide (TPP) as different titanium alkoxide precursors. The as-prepared composites were characterized by BET surface area, SEM, XRD, EDX and UV-visible absorption spectroscopy. The samples were evaluated for their photocatalytic activity towards the degradation of methylene blue (MB) under UV irradiation. The results indicated that the sample GTNB had best excellent photocatalytic activity among the three kinds of samples. According to the photocatalytic results, methylene blue removal by a treatment with graphene/TiO2 composites seems to have an excellent removal effect as order of GTIP, GTNB and GTPP composites due to a photolysis of the supported TiO2, the radical reaction and the adsorptivity and absorptivity of the graphene.